2020
DOI: 10.1021/acs.energyfuels.0c01573
|View full text |Cite
|
Sign up to set email alerts
|

Model Lignin Oligomer Pyrolysis: Coupled Conformational and Thermodynamic Analysis of β-O-4′ Bond Cleavage

Abstract: The abundance, carbon content, and functionalized nature of lignin make it a promising candidate for targeted valorization to fuels and polymer composites. While lignin modeling by the application of computational chemistry is an active area of research, electronic structure methods have been limited mainly to structures in the dimeric or trimeric range. In this study, we have modeled a lignin structure composed of 10 β-O-4′ linked guaiacyl (G) units, such that this work represents, to the best of our knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…The various interunit bonds connecting lignin monomers have a range of bond dissociation enthalpies. Ether linkages, such as β-O-4, tend to be ∼60–70 kcal/mol, while C–C bonds tend to be ∼100 kcal/mol. The location of a given bond in a lignin oligomeric unit can also have an impact on its dissociation enthalpy for β-O-4 homolytic cleavage . Because of bond dissociation enthalpy disparities between C–O and C–C bonds, during the early stages of pyrolysis, there should be preferential cleavage of ether linkages. , During these primary reactions (e.g., ether cleavage, demethoxylation, decarboxylation, and deacylation) that result in deoxygenation and molecular weight decreases for initial MWL, oligomers with a sufficiently low vaporization temperature are formed and subsequently devolatilized directly from the reaction front.…”
Section: Discussionmentioning
confidence: 99%
“…The various interunit bonds connecting lignin monomers have a range of bond dissociation enthalpies. Ether linkages, such as β-O-4, tend to be ∼60–70 kcal/mol, while C–C bonds tend to be ∼100 kcal/mol. The location of a given bond in a lignin oligomeric unit can also have an impact on its dissociation enthalpy for β-O-4 homolytic cleavage . Because of bond dissociation enthalpy disparities between C–O and C–C bonds, during the early stages of pyrolysis, there should be preferential cleavage of ether linkages. , During these primary reactions (e.g., ether cleavage, demethoxylation, decarboxylation, and deacylation) that result in deoxygenation and molecular weight decreases for initial MWL, oligomers with a sufficiently low vaporization temperature are formed and subsequently devolatilized directly from the reaction front.…”
Section: Discussionmentioning
confidence: 99%
“…The main repeating units, which are coumaryl alcohol, coniferyl alcohol, and sinapyl alcohol, form the three types of segments within lignin: p -hydroxyphenyl, guaiacyl, and syringyl. , These materials contain numerous functional groups: aliphatic and phenolic hydroxyl, carboxylic, carbonyl, methoxy groups, and covalent linkages. The important carbon–oxygen links in lignin are β-O-4, α-O-4, and 4-O-5, and carbon–carbon linkages are β-5, 5–5, β-1, and β–β linkages. , …”
Section: Introductionmentioning
confidence: 99%
“…The important carbon−oxygen links in lignin are β-O-4, α-O-4, and 4-O-5, and carbon−carbon linkages are β-5, 5−5, β-1, and β−β linkages. 6,8 Although lignin possesses important properties as a raw material of polymers, 2 it has poor solubility in organic solvents when lignin is produced on a large scale due to its irregularly networked chemical structure and high concentration of aromaticity. The poor solubility and not well-defined chemical structure of lignin are the most significant challenges for ligninbased polymer synthesis and characterization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The interactions between bonded atoms were subsequently optimized with respect to quantum chemical vibrational data using the Automated Frequency Matching Method developed by Vaiana et al [24]. It was found that dihedral rotations around the β-O-4 linkage within the lignin structure played a significant role in determining the configuration of the lignin macromolecule [25,26]. Petridis et al studied two equivalent dihedrals in lignin model system for showing the dihedral rotations [23].…”
Section: Figure 2 Lignocelluosic Unit Constructed Bymentioning
confidence: 99%